2006
DOI: 10.1359/jbmr.060118
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Prenylation by Bisphosphonates Causes Sustained Activation of Rac, Cdc42, and Rho GTPases

Abstract: N-BPs, which inhibit bone resorption by preventing prenylation of small GTPases, unexpectedly cause the accumulation of GTP-bound, unprenylated Rho family GTPases in macrophages and osteoclasts. In macrophages, this also leads to sustained, Rac-mediated activation of p38. The antiresorptive activity of N-BPs may therefore be caused at least in part, by the accumulation of unprenylated small GTPases, causing inappropriate activation of downstream signaling pathways.Introduction: Nitrogen-containing bisphosphona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(125 citation statements)
references
References 45 publications
(55 reference statements)
9
113
0
3
Order By: Relevance
“…Anesthetized mice were injected intravenously with 100 mL phosphate-buffered saline (PBS) containing 2 nmol of dissolved OsteoSense750EX (PerkinElmer, Waltham, MA, USA), a fluorescently conjugated pamidronate derivative, (21) and imaged 2,4,6,8,10,15,20, and 30 minutes after injection using the NightOwl planar imaging system (Berthold Technologies, Bad Wildbad, Germany) to qualitatively determine kinetic distribution. A phantom was placed over the mouse bladder to help position the limbs and prevent obscuring of the limb signal from the urinary pool of bisphosphonate.…”
Section: Bisphosphonate Binding Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anesthetized mice were injected intravenously with 100 mL phosphate-buffered saline (PBS) containing 2 nmol of dissolved OsteoSense750EX (PerkinElmer, Waltham, MA, USA), a fluorescently conjugated pamidronate derivative, (21) and imaged 2,4,6,8,10,15,20, and 30 minutes after injection using the NightOwl planar imaging system (Berthold Technologies, Bad Wildbad, Germany) to qualitatively determine kinetic distribution. A phantom was placed over the mouse bladder to help position the limbs and prevent obscuring of the limb signal from the urinary pool of bisphosphonate.…”
Section: Bisphosphonate Binding Kineticsmentioning
confidence: 99%
“…(8,9) This results in the accumulation of unprenylated proteins with aberrant functions within the cell. (10) With the conjugation of infrared and near-infrared fluorescent dyes, bisphosphonates are now being assessed for their utility as a tool for monitoring bone dynamics in preclinical models.…”
Section: Introductionmentioning
confidence: 99%
“…osteoblast and osteoclast exposure to aln and pamidronate was found to result in the activation of caspase-3 and the activation of the p38 MaPK and JnK signaling pathways (40). Dunford et al recently reported that BPs cause apoptosis and activate the MaPK and JnK signaling pathways in osteoclasts and J774 macrophages in vitro (19). JnK induces cell apoptosis by phosphorylation and activation of the transcription factor p53 (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of protein prenylation may affect many proteins found in an osteoclast, influencing osteoclastogenesis, cell survival and cytoskeletal dynamics (15)(16)(17)(18). BPs also cause apoptosis and activate the MaPK and c-Jun n-terminal kinase (JnK) signaling pathways in osteoclasts and J774 macrophages in vitro (19). Various studies have shown that JnK induces cell apoptosis by phosphorylation and activation of the transcription factor p53 (20,21) or by phosphorylation (and inactivation) of the anti-apoptotic proteins of the Bcl-2 family (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Non-amino bisphosphonates disrupt the ATP metabolic pathway in osteoclasts that leads to osteoclast apoptosis, while the amino bisphosphonates impair FPPS. This inhibitory effect on FPPS leads to reduced osteoclast capacity to prenylate specific intracellular proteins necessary for normal osteoclastic cell function (5). The end result is a reduced ability of osteoclasts to induce bone resorption and to induce programmed cell death (apoptosis) of osteoclasts ( Figure 1).…”
Section: Mechanism Of Actionmentioning
confidence: 99%